IMPACT OF REMOTE WORKING ON THE PERFORMANCE OF EMPLOYEES AND BUSINESS POST COVID-19. THE MODERATING ROLE OF JOB CRAFTING - Dr. Ana Atta (International Journal of Contemporary Issues in Social Sciences, 2024)
The COVID-19 outbreak brought in widespread remote employment which play a key role in transforming the workplace. The study examined the impact of remote working performance of employees and business performance post COVID-19 with a focus of job crafting as a moderating variable. 385 employees from an IT sector Karachi, Pakistan were recruited and surveyed by the researcher through convenience sampling method. The collected using Smart PLS as Confirmatory Factor Analysis (CFA) and Structure Equation Modelling were utilised (SEM). The study found that remote working significantly enhances employee performance and business performance (β = 0.42, p < 0.01). Through the role of job crafting, it was discovered that the variables significantly affects the relationship between remote working and employee business performance (β = 0.29, p < 0.01, β – 0.25, p < 0.05). The findings resulted in an increase in both productivity and employee satisfaction. As per the findings of the study, efforts to create new jobs have the potential to improve the outcomes of remote work for both employee and businesses. It is recommended that organizations must understand how remote work, job crafting, and performance outcomes interact in today's changing workplace. They should encourage WFH as job crafting, which can greatly increase employee and corporate performance.